Remineralization effectiveness of the PAMAM dendrimer with different terminal groups on artificial initial enamel caries in vitro. Issue 2 (February 2020) - Fan, Menglin; Zhang, Min; Xu, Hockin H.K.; Tao, Siying; Yu, Zhaohan; Yang, Jiaojiao; Yuan, He; Zhou, Xuedong; Liang, Kunneng; Li, Jiyao
Abstract: Objective: Disruption of the demineralization–remineralization balance could trigger the development of dental caries, making it challenging for enamel to "self-heal". Thus, extrinsic assistance is needed to restore enamel lesions and stop undermining progression. The aim of this study was to investigate enamel remineralization in a simulated oral environment via poly (amino amine) (PAMAM) dendrimers quantitatively. Methods: Bovine enamel specimens were shaken in demineralization solution (pH 4.5, 37 °C, 50 rpm/min) for 72 h to create initial enamel carious lesions. The subsurface-demineralized specimens were then divided into four groups: enamel treated with PAMAM-NH2, enamel treated with PAMAM−COOH, enamel treated with PAMAM−OH, and enamel treated with deionized water. The treated specimens underwent subsequent 12-day pH cycling. Enamel blocks were analyzed by transverse microradiography (TMR), surface microhardness testing and scanning electron microscopy (SEM) before and after demineralization and pH cycling. Results: Groups treated with PAMAM dendrimers showed lower lesion depth and less mineral loss, attained more vertical-section surface microhardness recovery, and adsorbed more mineral deposits (p < 0.05). The enamel lesion remineralization values of PAMAM-NH2, PAMAM-COOH, and PAMAM-OH groups were 76.42 ± 3.32%, 60.07 ± 5.92% and 54.52 ± 7.81%, respectively. Significance: In conclusion, PAMAM with different terminal groups could induce enamel remineralization, among which PAMAM-NH2 showed the most prominent competence, followed by PAMAM-COOH and PAMAM-OH, in that order.